The zero-leverage puzzle : evidence from portuguese firms - Portugal, Maria Ferro Barreto Candeias (2021)
The main objective of this paper is to identify the characteristics of Portuguese firms that have no debt in their capital structure and to understand what are the motivations behind such choices. After that, it aims at understanding if zero-leverage policies predict differences in performance during crisis periods. Using a rich source of high-quality balance sheet data for non-listed and listed Portuguese firms for the period 2006–2018, this study focuses on zero-leverage policies through an empirical analysis of 1,174,151 firm-year observations. We first present evidence that zero-leverage firms are commonly small and young and show lower levels of profitability and tangibility, when compared to their levered counterparts. Moreover, firms with no debt hoard large cash reserves and are found to have higher liquidity ratios than those of levered firms. Furthermore, we confirm that there are different motives for firms to eschew debt financing. On the one hand, findings suggest that micro firms and SMEs are financially constrained, having difficulties in accessing debt markets. On the other hand, larger firms seek for financial flexibility, in order to avoid debt overhang and preserve leverage capacity, when opting for zero-leverage policies. Additionally, we study performance levels of companies that adopt zero-leverage policies to assess if such behaviours help improving the overall firms’ functioning after crisis periods. We acknowledge moderate support for our main premise that zero-leverage firms overperform their levered counterparts, during and after crisis periods.